2018
DOI: 10.1101/430413
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Infiltration of CD8+ T cells into tumor-cell clusters in Triple Negative Breast Cancer

Abstract: Infiltration of CD8 + T lymphocytes into solid tumors is associated with good prognosis in various types of cancer, including Triple Negative Breast Cancers (TNBC). However, the mechanisms underlying different infiltration-levels are largely unknown. Here, we have characterized the spatial profile of CD8 + T cells around tumor-cell clusters in the core and margin regions in TNBC. Combining mathematical modeling and data analysis, we propose that there exists a possible chemo-repellent inside tumor-cell cluster… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…Collagen fiber orientation was described as the coefficient of variation (CV) of the angle for all fibers, the smaller the CV is, the more aligned the fibers are. Fibers in non-treated tumors remained mainly oriented in one dominant direction (Figures 3B, 3C and 3F) with a CV from 1.85 to 0.5 consistent with previous findings (35). LOX inhibition tends to disrupt the alignment of collagen fibers, meaning that they were more dispersed and oriented in different directions with increased CV as compared to control conditions.…”
Section: Lox Modulates Tumor Stiffness and The Ecm Organizationsupporting
confidence: 89%
See 1 more Smart Citation
“…Collagen fiber orientation was described as the coefficient of variation (CV) of the angle for all fibers, the smaller the CV is, the more aligned the fibers are. Fibers in non-treated tumors remained mainly oriented in one dominant direction (Figures 3B, 3C and 3F) with a CV from 1.85 to 0.5 consistent with previous findings (35). LOX inhibition tends to disrupt the alignment of collagen fibers, meaning that they were more dispersed and oriented in different directions with increased CV as compared to control conditions.…”
Section: Lox Modulates Tumor Stiffness and The Ecm Organizationsupporting
confidence: 89%
“…Likewise, in aged skin, dermal fibroblasts harbor a phenotype similar to CAFs and produce ECM matrices that limit T cell displacements (43). However, in triple-negative breast cancers and in pancreatic tumors T cells were still found in dense networks of collagen fibers (35,44). Since most of the aforementioned studies were correlative, we decided in this study to specifically alter the ECM network by LOX inhibition and investigated the consequences on T cell motile behavior.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is well known that the higher the density of TILs and leukocytes infiltrating into cancer cell islands, the better the prognosis. The "inflamed" tumors were associated with a better response to immunotherapy than the "noninflamed" and "immune-excluded" tumors (12,(30)(31)(32)(33). Similarly, we find that higher densities of B cells as well as CD8 + and CD3 + T cells (and Th cells and Tregs to a lesser extent) in the cancer cell islands are also correlated with improved prognosis (Fig.…”
Section: Nearest Neighbor (Nn) Distances Between Cells Of a Given Typesupporting
confidence: 63%
“…This indicates that differences in physical topography may not be the explanation. It may be that CD20 + B cells, CD8 + T cells and CD3 + T cells in good outcome patients are more responsive to chemokines secreted by tumor cells and are more successful in finding their cognate antigens within the tumor microenvironment as in a recently published study (36).…”
Section: Discussionmentioning
confidence: 88%
“…29 Therefore, it is crucial to measure the extent of CD8+ T cell infiltration of solid tumors. 30 Our GSVA analysis also demonstrated that enrichment of the antigen processing pathway (P = 0.01), and possibly the lymphocyte activation pathway (P = 0.08), correlated with better prognosis ( Figure S1). The antigen processing pathway prepares antigens by converting them into MHC-I bound peptides for presentation to T lymphocytes.…”
Section: Dovepressmentioning
confidence: 60%